Potential Key Factors, Policies, and Barriers for Rooftop Agriculture in EU Cities: Barcelona, Berlin, Bologna, and Paris - Zambrano-Prado, Perla; Orsini, Francesco; Rieradevall, Joan; Josa, Alejandro; Gabarrell, Xavier (Frontiers in Sustainable Food Systems, 2021)
The main objective of this study is to contribute a framework and to provide an overview of potential key factors, policies, and barriers associated with the integration of rooftop urban agriculture (RUA), building on stakeholders' perspectives in four European cities (Barcelona, Berlin, Bologna, and Paris). The research was developed in two phases, namely, a workshop and a survey of stakeholders involved in RUA from the four cities. Education, environmental, research, technological innovation, food production, and social factors play an important role in implementing RUA. Productive spaces, cultural values, social cohesion, social rural-urban links, and the high cost of urban land are highlighted as factors that “promote” RUA. In contrast, the cost of water and pollution are major contextual factors that constrain RUA. Policies related to food trade and urban planning are those that most limit RUA development. Major architectural and technical barriers related to the limits on building heights, historical buildings, a lack of specific building codes, building design and roof accessibility were identified. The high cost of infrastructure and policies that prohibit RUA product sales emerged as economic constraints. Major differences among the cities studied included the perceived effect of urban policies on RUA diffusion as well as the perceived relevance of economic and pollution factors. This study revealed that extensive dissemination and the development of appropriate information about RUA are needed. The creation of new regulations, as well as modifications to urban and building codes to support RUA, is also envisaged. This approach will consider a more flexible land-use policy that allows agriculture to take place in cities as well as marketing frameworks for RUA products. For future studies, it would be useful to apply the framework developed in this study to a larger sample. A study is also needed to confirm hypothetical differences between cities.